Alternativas de solución como propuesta de base para la estructuración de una plataforma virtual bajo el modelo de negocio b2b a favor de micro y pequeñas empresas manufactureras con potencial exportador en Palmira (2021)
Small and Micro companies represent one of the largest sectors in the country's economy and the manufacturing sector is very dynamic with a high potential for productivity and employability, this has made small and micro companies have been strengthening over time, but at the same time they present obstacles that slow down their operations and the need to acquire more clients. In this sense, the objective is to propose alternative solutions that lead to the structuring of a virtual platform, under the B2B Business model in favor of the international dynamics of Micro and Small manufacturing companies with export potential. The method was quantitative, with a descriptiveexploratory approach; Since it describes all the problems associated with business between national companies and foreign companies in the manufacturing subsector for Micro and Small companies conglomerates, because, although there are studies related to structuring virtual platforms, they have not been applied to the Palmira region, this being the area under study. As a result, it was detected that the micro manufacturing companies have problems such as ignorance about what taxes they should pay in case they have to, also the costs at the time of wanting to export in addition to the procedures among some others; Therefore, it is concluded that proposing alternatives that lead to promoting the structuring of a platform in favor of micro and small companies puts them at the level of large companies, because they could improve their products and teach them to the foreign market. In short, the platform must be created in the future, because doing so would greatly help these companies that have the need but do not have enough support to achieve it.